Life History Strategies of the Winter Annual Plant Echinops gmelinii (Asteraceae) in a Cold Desert Population - Yanli Wang; Xinrong Li; Jiecai Zhao (Plants)
Echinops gmelinii Turcz. is a winter annual species of the Asteraceae family, distributed in sandy areas of northern China, and is crucial for wind avoidance and sand fixation. To understand the inter- and intra-annual population dynamics of E. gmelinii in its cold desert habitats, we conducted long- and short-term demographic studies to investigate the timing of germination, seedling survival, soil seed bank and seed longevity of natural populations on the fringe of the Tengger Desert. Cypselae (seeds) of E. gmelinii can germinate in both July and August, but this process is heavily affected by precipitation amount and timing. Early emerging seedlings died rapidly under the high temperature and drought stress, before completing their life cycle. Later emerging seedlings could survive to complete their life cycle due to more suitable conditions for plant growth. In short, seedling survival dynamics were affected by precipitation distribution, and the survival rates were low (<4%). In addition, we found that the high seed production (1328 seeds·m−2) of E. gmelinii depended mainly on the production of seeds by individuals rather than high plant density (35 individuals·m−2). The contribution of newly ripened seeds and soil seed banks to seedlings emergence was 57.7% and 42.3%, respectively. Thus, only a small amount of the newly matured seeds was depleted during the year. Only 23.6% of the annual seeds germinated, and the remainder accumulated in a persistent soil seed bank (seed longevity was ≥2 y). The amount and timing of precipitation distribution were the key factors affecting the population dynamics of E. gmelinii in our study area. This species can cope with the uncertain precipitation patterns though a “cautious” germination strategy, varying the timing of germination and forming a persistent soil seed bank.